




//
Just double check that I did the right calculations
Answer:
We have the sentence:
"X by the power of 5 times y to the power of 6 over 2 by the power of -2 times x by the power of 0times x by the power of 9"
Let's break it into parts.
"X by the power of 5 times y to the power of 6..."
This can be written as:
x^5*y^6
"... 2 by the power of -2 times x by the power of 0times x by the power of 9"
This can be written as:
2^(-2)*x^(0)*x^(9)
And we have the quotient between the first thing and the second thing, then the equation is:

And any number by the power of 0 is equal to 1, then:
x^0 = 1, then we can rewrite the equation as:

We can keep simplifying this.
We know that:
a^(-n) = (1/a)^(n)
Then:
2^(-2) = (1/2)^2 = 1/4
Then we get:

And we also know that:
a^n/a^m = a^(n - m)
Then:

And we can't simplify this anymore.
X=7/64 you multiply them by x first then do the math
Answer:
x=2 y=1
Step-by-step explanation:
Solve the equations by substituting y=6x-11 into -2x-3y=-7.
-2x-3(6x-11)=-7
-2x-18x+33=-7
-20x+33=-7
-20x=-7-33
-20x=-40
x=2
To find y, substitute this value into the equation and solve for y.
y=6(2)-11
y=12-11
y=1